A novel Lucas-based adaptive sampling optimization for enhancing network lifetime - Kanaka Raju Rajana; Shanmuk Srinivas Amiripalli (Institute of Advanced Engineering and Science, 2026)
This paper introduced to enhance network lifetime using a novel Lucas based adaptive sampling methodology by sampling network condition to dynamically modifying sampling intervals using the Lucas sequence, this sequence not only used for sampling but also used to modify data collection, optimizing accuracy and energy efficiency. This technique aims to reduce superfluous data transmissions and conserve network resources by monitoring network utilization and adjusting sample with low medium and high rates. We enhance the network performance and longevity using Lucas based technique via simulation and demonstrating its potential. This may effectively approach novel address to challenges associated with constrained networks, particularly in the domain of IoT and wireless sensor networks (WSNs).